Newtonian Yoyo (Lato-Lato) Phenomenon in Indonesia: An Innovative Resource for IGCSE Physics Teaching and Learning? - Hamdi Akhsan; Guruh Sukarno Putra; Melly Ariska (Universitas Negeri Jakarta, 2023)
This paper aims to stimulate a teaching and learning reflection for Indonesian IGCSE physics classrooms through a recent booming and recreational game of Newtonian yoyo called lato-lato. As physics is one of the critical and complex subjects in secondary school, it establishes a struggle for students to comprehend the concept of physics. The 21st-century physics education learning aims to promote high-end reasoning and deep understanding. Contextual physic learning will support this mission to reach maximum attainment for students. Physics through contextual knowledge will be more feasible for students. The recent phenomenon of lato-lato encounters a new interest for students. Lato-lato as a demonstrator and contextual example will be a resourceful material for several concepts of Newtonian mechanics, for instance: collision and energy. In addition, lato-lato may provide an advanced idea of circular motion, momentum, and impulse, oscillation. Lato-lato involvement may bring a chance for IGCSE curriculum adjustment in mechanics topics to become a significant pre-learning process. By using the adjusted curriculum, students are more likely to reach their maximum attainment and conceptual understanding of mechanics because students feel interested and encouraged to learn through a problem-solving and real-world setup. Lato-lato (Newtonian Yoyo) phenomenon may solve students' learning difficulties in IGCSE physics through a conceptual phenomenon.